The History Of The Irrigation System In Uzbekistan (Texas Journal of Multidisciplinary Studies, 2024)
The article analyzes on the basis of primary sources, scientific literature, Internet materials and statistical data the issues of significant attention to modernizing the irrigation system of Uzbekistan over the years of independence, providing the industry with modern equipment, protecting water resources, reclamation of irrigated lands, reconstruction, repair of hydraulic structures and increasing year to year capital investment. The research also highlights the important reforms and a number of measures taken in the water management system after the independence of Uzbekistan, as in all areas